Mathematical rationale for creating an application for conducting random meetings "Coffee Break" - Ziuziun, Vadym Ihorovych; Osoka, Daniil Serhiiovych (Національний технічний університет "Харківський політехнічний інститут", 2024)
Modern society is facing an increasing trend of social isolation, as people increasingly rely on social media for interaction instead of face-to-face communication. This lack of in-person contact often leads to feelings of loneliness and disconnection. This study proposes the concept of a mobile application, CoffeeBreak, designed to counteract these trends by offering users a platform to arrange brief, in-person meetings, such as a quick coffee. The model ensures that users are matched in a way that promotes engagement, as each participant can be assured that their matched partner is equally motivated for the encounter. As the application continues to evolve, it can incorporate additional scheduling criteria to enhance the quality of matches and distribution. For example, if a user attends a meeting within the first two days, they could unlock the potential for additional matches by the end of the week. Ultimately, CoffeeBreak aims to broaden users' horizons, help them form new professional and informal connections, and enhance their social skills.

Сучасне суспільство зіштовхується зі зростаючою тенденцією соціальної ізоляції, оскільки люди все більше покладаються на соціальні мережі для взаємодії замість спілкування віч-на-віч. Відсутність особистого контакту часто призводить до почуття самотності та відірваності. У цьому дослідженні пропонується концепція мобільного додатку CoffeeBreak, розробленого для протидії цим тенденціям, пропонуючи користувачам платформу для організації коротких особистих зустрічей, наприклад, швидкої бесіди за кавою. Заохочуючи користувачів зустрічатися в реальному житті, програма спрямована на розвиток значущих соціальних зв'язків і боротьбу з почуттям ізоляції, поширеним у сучасному цифровому світі. Основна інновація додатку CoffeeBreak полягає в його унікальному підході до пошуку партнерів. Зрештою, CoffeeBreak має на меті розширити кругозір користувачів, допомогти їм створити нові професійні та неформальні зв'язки та покращити їхні соціальні навички.
Математичне обґрунтування створення додатку для проведення випадкових зустрічей "Coffee Break"
Keywords: mathematical models; random meetings; socialization; networkings; information systems; мобільні додатки; інформаційні системи; математичні моделі; соціалізація; випадкові зустрічі; нетворкінг